Bases for an Educational Model Structured on Tourism Competencies as a Tool for Tourism Development (Revista LIDER, 2019)
The continuous growth of tourism in Peru, as well as the positive projections of this activity at the international level and the development of new emerging tourism markets, oblige countries to work on new educational strategies to form human talent according to the needs of the tourism industry and efficiently serve an increasingly demanding tourist. This document will focus on those theoretical aspects used for the design and strengthening of a model of higher education in tourism, which takes into account trends in tourism in higher education. A methodology based on a case study has been applied, with the purpose of presenting a training model in higher education in tourism and its implications. For the development of the stages related to the proposal of the formative model, the methodological experience suggested by the World Tourism Organization on human capital has been considered. The model pursues the search for new talents capable of covering the needs and demands of the productive sector. This educational process will allow for the planning and the execution of an educational policy in tourism in Peru and in other countries that are on the same path of designing a strategy of higher education for this activity. It is concluded that it is necessary to make adjustments in higher education to constantly adapt to the way knowledge and content should be imparted, since these are changing environments. The established proposal, serves as a base and a platform, but it must be renewed with certain periodicity, according to the circumstances, without neglecting the evaluation, measurement and monitoring of the educational system.